Improvement of Nutrient Uptake, Yield of Black Sesame (Sesamum indicum L.), and Alluvial Soil Fertility in Dyke by Spent Rice Straw from Mushroom Cultivation as Biofertilizer Containing Potent Strains of Rhodopseudomonas palustris - Nguyen Quoc Khuong; Le Vinh Thuc; Cao Tien Giang; Ly Ngoc Thanh Xuan; Le Thi My Thu; Akagi Isao; Sakagami Jun-Ichi (The Scientific World Journal)
The aim of the current research was to evaluate the effects of members of purple nonsulfur bacteria (PNSB), Rhodopseudomonas palustris strains of VNW02, TLS06, VNW64, and VNS89, mixed with spent rice straw (SRS) from mushroom cultivation as a carrier on promoting sesame growth and yield, and ameliorating the alluvial soil (AS) fertility in dykes. A 4 × 3 factorial experiment consisting of different levels of the solid PNSB biofertilizer mixture at 0, 3, 4, and 5 t·ha−1 (0, 1.81 × 108, 2.24 × 108, and 2.68 × 108 cells pot−1, respectively), and nitrogen (N) and phosphorus (P) inorganic fertilizer rates (100, 75, and 50 kg·N·ha−1; 60, 45, and 30 kg P2O5·ha−1, respectively) was performed in pots with the sesame variety of ADB1 in the dyked AS. The solid PNSB biofertilizer mixture at at least 3 t·ha−1 significantly enhanced the sesame seed yield by providing higher macronutrients for plants by increasing available N and soluble P concentrations in the soil. The solid PNSB biofertilizer mixture in addition to 75% of the recommended N and P fertilizers produced an equivalent yield in comparison to the utilized 100% of N and P inorganic fertilizers. The solid PNSB biofertilizer mixture in the SRS from the mushroom production reduced at least 25% of N and P chemical fertilizers for gaining the maximal seed yield and enriched soil characteristics for the sustainable black sesame cultivation in the dyked AS.